2017
DOI: 10.1177/0884533617725071
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Patient‐Generated Subjective Global Assessment (PG‐SGA) in Patients With Advanced Cancer in Palliative Care

Abstract: The scored PG-SGA is an independent prognostic factor of survival and thus can be a useful tool for nutrition evaluation in palliative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 32 publications
2
23
1
1
Order By: Relevance
“…The PG-SGA is the reference tool for oncology patients' nutritional assessment and is a sensitive, comprehensible, easy and quick tool to assess malnutrition [42,43]. Correcting for short-term improvements in weight and scoring multiple nutrition impact symptoms, it offers high accuracy in distinguishing well-nourished from malnourished patients; however, it ultimately categorises more patients at risk compared to other tools [44,45]. To the best of our knowledge, there have not been other studies assessing nutritional risk in cancer patients using the NST; therefore, comparison of the prevalence of patients identified as at risk of malnutrition using the NST with similar studies is disadvantaged.…”
Section: Discussionmentioning
confidence: 99%
“…The PG-SGA is the reference tool for oncology patients' nutritional assessment and is a sensitive, comprehensible, easy and quick tool to assess malnutrition [42,43]. Correcting for short-term improvements in weight and scoring multiple nutrition impact symptoms, it offers high accuracy in distinguishing well-nourished from malnourished patients; however, it ultimately categorises more patients at risk compared to other tools [44,45]. To the best of our knowledge, there have not been other studies assessing nutritional risk in cancer patients using the NST; therefore, comparison of the prevalence of patients identified as at risk of malnutrition using the NST with similar studies is disadvantaged.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, according to the SGA, 84.84% of patients were evaluated as malnourished (SGA B + C), while 42.42% subjects of all participants were severe malnourished (SGA C). Similarly, Wiegert et al evaluated the nutritional status of advanced cancer patients in palliative care (n = 120) in Brazil using PG-SGA [16]. It was shown that, 94.2% patients were malnourished [16].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Wiegert et al evaluated the nutritional status of advanced cancer patients in palliative care (n = 120) in Brazil using PG-SGA [16]. It was shown that, 94.2% patients were malnourished [16]. Moreover, another trial including 172 advanced cancer patients also in Brazil, showed that 83.6% of these patients were malnourished (PG-SGA B + C) [17].…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional status was assessed using Subjective Global Assessment (SGA) 4 . We assessed this patient had B on his SGA score.…”
Section: Casementioning
confidence: 99%
“…Nutritional screening should be performed regularly to all cancer patients as early nutrition status evaluation and assessment 3,4 . It is expected that nutritional therapy could improve biochemical values such as serum albumin levels and kidney function.…”
Section: Introductionmentioning
confidence: 99%